A novel sustained release drug–resin complex-based microbeads of ciprofloxacin HCl. (16th November 2016) - Jain, Sunil K.; Prajapati, Neeraj; Rajpoot, Kuldeep; Kumar, Amrish
Abstract: Objective A novel multiparticulate system for the gastro-mucoadhesive delivery of ciprofloxacin HCl (CFN) was developed with the help of ion-exchange resin to deal with urinary tract (UT) infections effectively.Materials and methods An optimized complex (resinate) of CFN with sodium polystyrene sulfonate USP resin was prepared and entrapped within microbeads of sodium alginate and pectin. The developed systems were evaluated for drug entrapment efficiency, percentage of mucoadhesion and in vitro release patterns in simulated gastric fluid (pH 1.2).Results and discussion The interaction of the resin complex and polycation via alginate was consequently supported the formation of polyelectrolyte complex membrane. The in vitro drug release studies demonstrate that formulation without drug–resin complex (NRB) released the drug more swiftly than formulation containing drug–resin complex (DRC). This controlled release pattern of drug, resin complex containing microbeads was owed to complexation between drug and resin.Conclusion Preliminary results from the study suggested that this drug–resin complex-entrapped microbeads can be used to incorporate other antibiotic drugs and could be effective against UT infection. Such developed formulation could be subjected to in vivo studies in future in order to prove their efficacy for such type of infections.